Proceedings of the 9th International Conference on Fracture Mechanics of Concrete and Concrete Structures 2016
DOI: 10.21012/fc9.118
|View full text |Cite
|
Sign up to set email alerts
|

Cracking of SHCC due to reinforcement corrosion

Abstract: Abstract. Reinforcement corrosion is the most important deterioration mechanism affecting reinforced concrete infrastructures. After corrosion starts, expansive pressures are exerted onto the surrounding concrete, causing cracking and spalling of the cover concrete. The amount of cover cracking can possibly be reduced by using strain hardening cementitious composites (SHCCs). In this work, the ability of strain hardening cementitious composite to resist cracking due to corrosion of reinforcement is studied. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…12), which hinders free ions movement. This finding is consistent with the research of Šavija et al [13,48] Polarization resistance R P of specimen can be roughly determined from the summation of electrolyte resistance R s , cover resistance R c , and charge transfer resistance R ct [36]. As can be seen from table 3, R ct in both R/SHCC and R/C is several orders higher than R s and R c before cover cracking and thus dominates R P of specimen.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…12), which hinders free ions movement. This finding is consistent with the research of Šavija et al [13,48] Polarization resistance R P of specimen can be roughly determined from the summation of electrolyte resistance R s , cover resistance R c , and charge transfer resistance R ct [36]. As can be seen from table 3, R ct in both R/SHCC and R/C is several orders higher than R s and R c before cover cracking and thus dominates R P of specimen.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…The beneficial effect of fibres on controlling splitting cracks stemming from rebar corrosion has been mentioned in the literature in several occasions. Available results showed that using fibre reinforced concrete (FRC) may significantly delay the appearance of corrosion-induced cracks [6][7][8][9]. However, the amount of fibres used in those studies was relatively high (>= 1.5% vol.).…”
Section: Introductionmentioning
confidence: 99%